1993
DOI: 10.1200/jco.1993.11.5.943
|View full text |Cite
|
Sign up to set email alerts
|

Effective therapy for poor-prognosis non-Hodgkin's lymphoma with 8 weeks of high-dose-intensity combination chemotherapy.

Abstract: This brief but intensive therapy was effective in treating poor-prognosis patients with non-Hodgkin's lymphoma. With this therapy, patients with small noncleaved-cell lymphoma or Shipp's category 3 disease had treatment outcome similar to the group as a whole. This therapy was not well tolerated by patients older than 60 years, and should not be given to this subgroup. Verification of these results in a randomized trial setting is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…A number of studies have addressed this question by escalating the dose of one or more of the drugs used in the CHOP regimen. 11,[16][17][18][19] In general, this strategy has been met with limited success because early toxicity was substantial and time intervals between therapies had to be extended, a high incidence of early secondary MDS/AML was reported, and superior outcome could not be demonstrated. 20 This latter finding is also supported by the results of a recent study of the DSHNHL that compared 6 courses of standard CHOEP-21 with a dose-escalated version of this regimen (cumulative doses of cyclophosphamide and etoposide were 750 versus 1600 and 300 versus 600 mg/m 2 per cycle, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have addressed this question by escalating the dose of one or more of the drugs used in the CHOP regimen. 11,[16][17][18][19] In general, this strategy has been met with limited success because early toxicity was substantial and time intervals between therapies had to be extended, a high incidence of early secondary MDS/AML was reported, and superior outcome could not be demonstrated. 20 This latter finding is also supported by the results of a recent study of the DSHNHL that compared 6 courses of standard CHOEP-21 with a dose-escalated version of this regimen (cumulative doses of cyclophosphamide and etoposide were 750 versus 1600 and 300 versus 600 mg/m 2 per cycle, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Median survival for the entire group was 22 months, with a 5-year actuarial survival of 34% ± 6%. Age, gender, stage at presentation, the use of prior radiation therapy, the prior use of high intensity-brief duration chemotherapy, 16 the use of CBV as compared to CY-VP-TBI, and the use of 1200 cGy as compared to 1000 cGy as the TBI dose were not significantly associated with survival following transplantation. There was a trend for patients with T cell lymphoma to have better survival following transplantation than patients with B cell lymphoma; 5-year OS 56% ± 18% vs 31% ± 6% (P = 0.06).…”
Section: Survivalmentioning
confidence: 95%
“…[8][9][10] Various studies suggest that high-dose therapy, with or without stem cell support, of chemosensitive poor prognosis patients improves the percentage of patients achieving complete response as well as long-term survival. 4,[11][12][13][14][15][16] However there are currently no prospective randomized trials which have confirmed the benefit of high-dose therapy as firstline treatment of poor risk NHL patients. 2 Our primary aim was to determine the feasibility of an intensified induction therapy yielding a high response rate in young poor risk NHL patients, followed by high-dose consolidation in chemosensitive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various induction regimens derived from the original CHOP regimen have been evaluated in such patients, although alternate approaches incorporating etoposide have been used. 12,17 In this trial we chose to increase the doses of the two most active compounds, doxorubicin and cyclophosphamide, in combination with etoposide, which has shown its efficacy both as first-line therapy and in relapsing NHL patients. 17,18 Doxorubicin dose was limited to The only toxic death observed in the trial occurred on the first day of the first course in a patient who developed fatal tumor lysis syndrome, at the first dose level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation